ANALISIS KEMAMPUAN PENALARAN MATEMATIS PADA MATERI BARISAN DAN DERET SISWA KELAS XI SMK NEGERI 1 TOMA TAHUN PEMBELAJARAN 2020/2021 - Hesti Anjani Wau(1); Darmawan Harefa(2); Rohpinus Sarumaha(3) (Universitas Nias Raya, 2022)
This research is motivated by the low ability of students’ mathematical reasoning on the material of sequences and series. This study aims to describe the ability of mathematical reasoning, especially qualitative in the material of sequences and series. This study uses students’ research type with a descriptive research approach. The informants of this research were students of class XI SMK Negeri 1 Toma totaling 12 students. The data were analyzed by the steps of data collection, data reduction, data presentation, and drawing conclusions. The research instrument used was a test of students’ mathematical reasoning abilities with interviews. Based on the results of the research and discussion, the researcher concluded that class XI students of SMK Negeri 1 Toma had mathematical reasoning abilities in the low category. The research finding show that students are not able to perform mathematical manipulation; students are not able to draw conlussions, compile evidence, provide reasons or evidence for the correctness of the solution; students are not able to draw coclusions from statements; and students are not able to find patterns or properties of mathematical phenomena to make generalizations. Through this study, it is suggested that students’ mathematical reasoning abilities be further improved by increasing the number of exercises related to mathematical reasoning